Adjunctive phage therapy improves antibiotic treatment of ventilator-associated-pneumonia with Pseudomonas aeruginosa - Chantal Weissfuss; Jingjing Li; Ulrike Behrendt; Karen Hoffmann; Magdalena Bürkle; Chunjiang Tan; Gopinath Krishnamoorthy; Imke H. E. Korf; Christine Rohde; Baptiste Gaborieau; Laurent Debarbieux; Jean-Damien Ricard; et al. (Nature Communications)
Abstract Bacterial multidrug resistance poses an urgent challenge for the treatment of critically ill patients developing ventilator-associated pneumonia (VAP). Phage therapy, a potential alternative when conventional antibiotics fail, has been unsuccessful in first clinical trials when used alone. Whether combining antibiotics with phages may enhance effectiveness remains to be tested in experimental models. Here, we use a murine model of Pseudomonas-induced VAP to compare the efficacy of adjunctive phage cocktail for antibiotic therapy to either meropenem or phages alone. Combined treatment in murine VAP results in faster clinical improvement and prevents lung epithelial cell damage. Using human primary epithelial cells to dissect these synergistic effects, we find that adjunctive phage therapy reduces the minimum effective concentration of meropenem and prevents resistance development against both treatments. These findings suggest adjunctive phage therapy represents a promising treatment for MDR-induced VAP, enhancing the effectiveness of both antibiotics and phages while reducing adverse effects.